Washable Fabric Triboelectric Nanogenerators for Potential Application in Face Masks - Sang-Hwa Jeon; Yongju Lee; Swarup Biswas; Hyojeong Choi; Selim Han; Minseo Kim; Dong-Wook Lee; Sohee Lee; Hyeok Kim; Jin-Hyuk Bae (Nanomaterials, 2022)
In order to counteract the COVID-19 pandemic by wearing face masks, we examine washable fabric-based triboelectric nanogenerators (FTENGs). We applied the flash-spun nonwoven fabric (FS fabric) into the FTENGs, comparing the melt-blown nonwoven fabric (MB fabric) based FTENGs, which is conventionally studied in the field of energy harvesting. For reusability, all our proposed FTENGs are systematically investigated by controlling the washing conditions. After washing, the degradation ratio of the obtained output voltage is found to be only 12.5% for FS FTENGs, compared to the ratio of about 50% for the typical MB FTENGs. A rather small degradation ratio for FS fabric cases has resulted from less changed fabric structure after washing due to more dense fabric nature. Additionally, in order to improve the electrical characteristics of FS FTENGs. Note that the output voltage of FTENGs exhibits as much as 600 V.